Algorithmic Accounting: When Algorithms Take the Role in Accounting Decision-Making in Modern Organizations - Nuriyah Hanik Fatikhah (Dhana, 2026)
The proliferation of artificial intelligence, machine learning, and algorithmic systems is fundamentally transforming accounting decision-making across modern organizations. This study examines the adoption, effectiveness, and ethical implications of algorithmic accounting systems in Indonesian corporate entities. A mixed-methods design was employed, combining a quantitative survey of 356 accounting professionals from publicly listed companies on the Indonesia Stock Exchange (IDX) with qualitative case studies of six organizations. Results demonstrate that AI/algorithmic systems have achieved substantial penetration across key accounting functions, with the highest adoption rates in financial forecasting and analytics (82.6%) and managerial decision support (74.8%). Algorithmic decision-making significantly predicted decision quality improvement (β=0.541, p<0.001), with organizations in the financial services sector exhibiting superior AI integration outcomes. However, critical challenges persist, including algorithmic bias, accountability gaps, explainability deficits, and ethical tensions in managerial accounting. The study proposes a comprehensive Algorithmic Accounting Governance Framework (AAGF) to guide organizations in deploying AI decision systems responsibly. These findings extend the literature on AI in accounting and provide practical implications for organizations, regulators, and accounting standard setters navigating the algorithmic transformation of financial decision-making.